TO THE DETERMINATION OF THE "GAME" HUMAN BEING OF THE INFORMATION SOCIETY - Кунденко, Я. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The main purpose of this article is the philosophical definition of the concept of "playfulness", as the methodological foundation of socio-humanitarian research of this phenomenon in the context of the being of the modern person of the information society. In it, playfulness is defined as a specific psychological property that makes it possible to perceive the information space not as a threat but as a basis for development.